Decreased Estimated Glomerular Filtration Rate (eGFR), Not Proteinuria, Is Associated with Asymptomatic Intracranial Arterial Stenosis in Chinese General Population - Zhaoxia Li; Jinxin Li; Anxin Wang; Hua Pan; Shouling Wu; Xingquan Zhao (Scientific Reports, 2017)
Abstarct The relationship between chronic kidney disease (CKD), which is defined by declined estimated glomerular filtration rate (eGFR) and/or proteinuria, and asymptomatic intracranial arterial stenosis (ICAS) is largely unknown. We conducted a population-based, cross-sectional study by recruiting 5209 participants free of previous stroke, transient ischemic attack and coronary heart disease. eGFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula and proteinuria was estimated with urine dipstick. The presence of ICAS was assessed by transcranial color-coded Doppler (TCD). Out of the whole population, 684 (13.1%) participants suffered ICAS. After adjusting for the confounding factors, eGFR < 45 ml/min/m2 was an independent risk factor of asymptomatic ICAS (odds ratio [OR], 3.29, 95% confidence interval [CI], 1.67–6.51), but the trend was different between the two groups stratified by the age of 60 (P = 0.01). However, the association between proteinuria and asymptomatic ICAS was not statistically significant. In conclusion, declined eGFR, not proteinuria, is associated with asymptomatic ICAS in Chinese general population, especially in people over 60 years old.